1976
DOI: 10.1002/hlca.19760590806
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal Complexes with Bidentate Ligands Spanning trans‐Positions. I. The synthesis of 2,11‐bis(diphenylphosphinomethyl)benzo[c]‐phenanthrene, a ligand promoting the formation of square planar complexes

Abstract: The bidentate ligand 2,11‐bis(diphenylphosphinomethyl)benzo[c]phenanthrene (1) was synthesized from 2,11‐dimethyl‐benzo[c]phenanthrene (3) via the corresponding bromomethyl derivative 9. 3 was obtained from the cyclization with boron trifluoride etherate of 1,1‐di‐(p‐methylphenethyl)‐epoxyethane (7), which was prepared from 1,5‐di(p‐tolyl)‐pentan‐3‐one (6).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Chromatography on silica gel (MeOH/CH2Cl2, 0.75%) gave the lower-Rf, S-shaped isomer of 3 (400 mg, 35%) and the higher-Rf, C-shaped isomer of 3 (462 mg, 41%). For the C-shaped isomer: 1H NMR (250 MHz, CDCl3) 8 6.64 (br s, 2H, -NH), 4.78 (br s, 2H, -NH), 1.76 (s, 12H, Me), 1.41 (s, 18H, t-Bu), 1.32 (s, 18H, t-Bu).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatography on silica gel (MeOH/CH2Cl2, 0.75%) gave the lower-Rf, S-shaped isomer of 3 (400 mg, 35%) and the higher-Rf, C-shaped isomer of 3 (462 mg, 41%). For the C-shaped isomer: 1H NMR (250 MHz, CDCl3) 8 6.64 (br s, 2H, -NH), 4.78 (br s, 2H, -NH), 1.76 (s, 12H, Me), 1.41 (s, 18H, t-Bu), 1.32 (s, 18H, t-Bu).…”
Section: Methodsmentioning
confidence: 99%
“…A framework of sufficient size, rigidity, and convergency is necessary to constrain the chelating functionality in order to eschew adjacent cis sites in favor of more distant trans sites. Only a few trans-spanning ligands have been reported, Transphos being the most cited example (3,4). Previous trans ligands have all chelated metals through nitrogen (5) or phosphorus (6, 7) atoms of tetrahedral geometry and possess a more open U shape (Fig.…”
mentioning
confidence: 99%
“…Initial backbones consisted of simple long hydrocarbon chains, but the possibility of different coordination modes and oligomer formation rendered somewhat disappointing results [1][2][3][4]. A more promising option arrived at this early stage with a more sophisticated phenanthrene based backbone developed by Venanzi et al [5].…”
Section: Introductionmentioning
confidence: 98%
“…Mp Ͼ 250°C. 1 Diphenylphosphanyl-11,23-bis(4-tolyl)-25,26,27,28-tetrapropoxycalix[4]arene (5): A suspension of 4 (2.00 g, 2.15 mmol) and anhydrous NiBr 2 (0.28 g, 1.29 mmol) in PhCN (20 mL) was heated at 180°C for 1 h. After addition of Ph 2 POEt (2.8 mL, 12.9 mmol) at 180°C the reaction mixture was refluxed for a further 1 h. The solvent was evaporated to dryness. The residue was taken up in toluene (20 mL) and washed with NH 3 /H 2 O (5%, 4ϫ 50 mL) and H 2 O (2ϫ 50 mL).…”
Section: 17-dibromo-1123-(132-dioxaborinanyl)-25262728-tetrapmentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] In recent studies we have investigated the coordination of several calix [4]arenes bearing two phosphanyl groups on the distal positions, C5 and C17, of the calixarene backbone. [15,16] We found that with Ni II and Pd II these ligands (CALDIPs) resulted in cis-chelate complexes in which the P-M-P angles were significantly larger than 90°.…”
Section: Introductionmentioning
confidence: 99%